2011
DOI: 10.1086/662553
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin, Energy Budget, and Thermogenesis in Striped Hamsters Exposed to Consecutive Decreases in Ambient Temperatures

Abstract: Leptin has been found to be a direct participant in the regulation of both energy intake and energy expenditure in small mammals showing seasonal declines in body mass (M(b)) and fat mass, but its roles in an animal exhibiting seasonally increased thermogenesis and unchanged M(b) remain unclear. Serum leptin levels, energy budget, and thermogenesis were measured in striped hamsters exposed to consecutive decreases in ambient temperatures ranging from 23° to -23°C. Cold-exposed hamsters had significant increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 64 publications
3
14
0
Order By: Relevance
“…T a has significant effects on both BMR and NST max in many small mammals including striped hamsters [9,[17][18][19][20][21]40,41]. In the present study, striped hamsters significantly decreased BMR and NST max after being acclimated to a warm condition (30°C), which were lower by 30.3% and 53.8% at 30°C than those at 21°C, respectively.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…T a has significant effects on both BMR and NST max in many small mammals including striped hamsters [9,[17][18][19][20][21]40,41]. In the present study, striped hamsters significantly decreased BMR and NST max after being acclimated to a warm condition (30°C), which were lower by 30.3% and 53.8% at 30°C than those at 21°C, respectively.…”
Section: Discussionsupporting
confidence: 43%
“…Animals usually increase energy intake in cold conditions, while less food is consumed after being acclimated to warm conditions [17][18][19][20][21]. In the previous study on striped hamsters, we observed that a consecutive decrease in T a induced a significant increase in food intake [21].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Different correlations have been shown between serum leptin levels and body mass in many small mammals under cold acclimation. For example, positive correlation were reported for Meriones unguiculatus (Li et al, 2004), E. miletus (Zhu et al, 2010a(Zhu et al, , 2010b(Zhu et al, , 2012b and A. chevrieri (Zhu et al, 2011b(Zhu et al, , 2012c, but tree shrews showed a negative correlation (Zhang et al, 2011), while Cricetulus barabensis showed no variation (Zhao, 2011). Consequently, the exact role of leptin in regulating body mass remains largely unknown and complex in wild mammals (Zhang & Wang, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was not affected by cold stress or food restriction, and it was also not correlated with all the immunological parameters detected, implying glucose was not the reason for the changes of immune function in striped hamsters. Cold exposure increases thermogenic capacity and metabolic rate across many species, including striped hamsters (Li et al, 2001;Liu et al, 2009;Chi and Wang, 2011;Zhao et al, 2010;Zhao, 2011;Zhou et al, 2015). Although thermogenic capacity and metabolic rate were not measured in the present study, the competition for energy resources between immune responses and thermogenesis might also account for the suppression of humoral immunity in striped hamsters (Yang et al, 2011;Odegaard and Chawla, 2013;Evans et al, 2015).…”
Section: Discussionmentioning
confidence: 69%